SUBDIVIDING OF THE TERRITORY OF “EKRANAS” PLANT ACCORDING TO DANGEROUS POINT SUMMARY POLLUTION CODES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
According to factor analysis results of topsoil geochemical data it can he seen that the pollution on extremely contaminated territory of "Ekranas ” plant in Panevezys is polygenous, According to technogmity level four of the seven distinguished factors are technogenous: one of them Mo-Cr-Mn-Ni-Cu-W-Sn-Co-Ag is characteristic of metal processing enterprises, the second one Y-Cd-Zn - of electrical engineering, partly - metal processing, the third Sb-Pb-Sr-Ba-Li-U-As one - of special (kinescopes) glass production, the fourth La-Ce one - of its polishing. These paragenetic associations were used for determination of dangerous point summary pollution codes and subdivision of the territory of “Ekranas” plant into zones according to them.